STUDENT’S PERCEPTION OF USING TIKTOK APPLICATION FOR LEARNING ENGLISH VOCABULARY - Tommy Hastomo; Adella Ramadhanti; Fidelia Viana; Fitri Saftiah; Eni Dwi Marcela (Universitas Pamulang, 2022)
This research goal is to find out about students’ perceptions of using TikTok in learning English vocabulary, which was carried out in the second semester of English education at STKIP PGRI Bandar Lampung. This study is a descriptive quantitative study in which data were collected by filling out a questionnaire by 25 students. The study results found that almost all students showed a satisfactory reaction to the TikTok apps for English learning vocabulary, which can be seen from the percentage of the questionnaire they filled out as participants. The students also agreed that TikTok helps them in learning English vocabulary. They can use TikTok anytime and anywhere to learn English vocabulary. TikTok video allows them to choose the topic of vocabulary that students want to improve, and the students agree TikTok help the students easily memorize the new English vocabulary that students have learned.